EXTENT OF VIABILITY OF DACUS DORSALIS MAGGOTS INDIFFERENT HOSTS - SINGH, MEETU; AVASTHI, SANGEETA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
The fruit fly, Dacus dorsalis is the most serious pest of Indo-gangetic plain. Its rate of infestation varies in different fruits and vegetables. The present investigation is to study the maggots viability of D. dorsalis in guava, mango, cucumber, bottle gourd and sponge gourd. The experiment is carried out under the laboratory conditions and data are calculated in every five days from the onset of fruit fly, D. dorsalis in the experimental fruits and vegetables. The average percentage of D. dorsalis is calculated on the basis of data recorded between 25-30 days of setting the experiment. The affect of variation of temperature in laboratory also influenced the percentage viability of D. dorsalis maggots in fruits and vegetables. The result reveals that the maggots viability in the sequence with maximum in guava followed by sponge gourd, mango, bottle gourd and cucumber indicating the guava as the most preferred fruit host for D. dorsalis,